Effect of Cold in Combination with Indomethacin Suppository Administration on Analgesic Need after Chest Tube Removal - nahid Daryaei; mitra Payami Bousari; noraldin Moosavi Nasab; eskandar Nourizadeh (Zanjan University of Medical Sciences and Health Services, 2012)
Background and Objectives: Chest tube removal is a prompt painful procedure. The pain is gradually relieved after removal of the tube. Cold application in combination with the Indomethacin suppository administration may increase the duration for analgesic need. This study aimed to evaluate the effect of cold in combination with Indomethacin suppository on the duration for analgesic need after chest tube removal. Materials and Methods: This quasi-experimental single-blinded study was conducted on 66 patients aged 18-68 years with chest tube in pleural space. The patients were randomly allocated into two intervention and control groups. In both groups, 100mg Indomethacin suppository was administered one hour before chest tube removal. In the intervention group, a 4ºc cold pack was applied in the chest tube side for 20 minutes. In the control group, the applied pack was in room temperature. The severity of pain was evaluated using the visual analogue score 20 minutes before and 15 minutes after the chest tube removal. The duration for analgesic need after chest tube removal was recorded in both groups. Results: Despite reduction, there was no statistically significant difference between the mean score of pain before the chest tube removal and 15 minutes after the procedure (p>0.05). After chest tube removal, patients in the control group requested for analgesic earlier than the patients in the intervention group. Conclusion: The application of cold in combination with the Indomethacin suppository increased the duration for analgesic need after chest tube removal. The application of cold in combination with the Indomethacin suppository is recommended as a solution to reduce the need for analgesic after chest tube removal.